Measuring serious violence perpetration: comparison of police-recorded and self-reported data in a UK cohort - Rosie Cornish; Alison Teyhan; Kate Tilling; John Macleod; Iain Brennan (International Journal of Population Data Science)
Introduction Determining risk factors and consequences of serious violence requires accurate measures of violence. Self-reported and police-recorded offending are subject to different sources of bias.